Assessment of the Tectonic Activity of the Muong La–Bac Yen–Cho Bo Fault (Northwest Vietnam) by Analysis of Geomorphological Indices - Phung Thi Thu Hang; Renat Shakirov; Bui Van Thom; Lê Van Dung; Nadezhda Syrbu; Tran Trung Hieu; Phung Thi Ngoc Anh; Tran Hoang Yen; Elena Maltseva; Andrey Kholmogorov; Nguyen Huu Tuyen; Vu Hoa An (GeoHazards, 2025)
The Muong La–Bac Yen–Cho Bo fault is one of the seismic faults in the northwest region of Vietnam. Neo-tectonic activities and exogenous processes have influenced the drainage system and topographic–geomorphologic features on both walls of the fault. The results of topographic analysis and geomorphological indices have confirmed the active tectonics of the fault during the Neo-tectonic period (Pliocene–Quaternary, about 5 million years). The valley floor width-to-height ratio (Vf) of less than 0.5 indicates the “rejuvenation” of the streams and the obvious influence of tectonic activities on the two walls of the studied fault. The Hypsometric curve (HC) in the study area has a straight–convex shape and the basins on the northeast wall have hypsometric integral index values ranging from 0.46 to 0.481, which are lower and more convex than those of the southwest wall. The Mountain-front sinuosity index (Smf) from 1.92 to 3.28 along the foot slope of the Hoang Lien Son range (the segment from Than Uyen to Bac Yen and Phu Yen) and the highly variable stream-length gradient index (SL) value on the northeast wall signify the relative tectonic uplift on the northeast wall of the fault. The deformed geomorphological indications (steep cliffs, slip surfaces, etc.) in the field confirm the active tectonics of the Muong La–Bac Yen–Cho Bo fault during the Neo-tectonic period.